Fatigue-induced inter-limb asymmetries in strength of the hip stabilizers, postural control and gait following a unilateral countermovement vertical jump protocol - Konstantopoulos, I.; Kafetzakis, I.; Chatziilias, V.; Mandalidis, D. (Sports, 2021)
It is generally accepted that neuromuscular overload and fatigue of one lower limb can affect the functional ability of the ipsilateral limb, and possibly the contralateral limb, increasing the likelihood of injury. The purpose of the current study was to examine the effect of a unilateral countermovement vertical jump (UCVJ) fatigue protocol on the neuromuscular function of the ipsilateral as well as the contralateral lower limb. The isometric strength of the hip stabilizers, postural control via posturographic analysis during the Y-Balance-Test (YBT), and the stance-phase-of-gait were assessed in 24 healthy physical active males and females before and after execution of a UCVJ fatigue protocol. The fatigue protocol included 5 sets of 20 maximum UCVJs performed on the supportive leg, with a 30-s break between sets. Following a 16.8% decline in vertical jump performance and an associated 2.3-fold increase in perceived exertion, our findings revealed significant post-fatigue inter-limb differences regarding postural control. The post-fatigue inter-limb differences regarding the isometric strength of the hip stabilizers and the stance-phase-of-gait parameters were not significant. Our findings showed that a 100 UCVJs session is likely to induce significant inter-limb differences in postural control, possibly increasing the risk of lower limb injury.